Use of Sorghum for Enhancing the Biodiversity and Nutritional Value of Semi-Desert Pasture Ecosystems - Bulakhtina, G K; Kudryashov, A V; Kudryashova, N I; Volodin, A B; Shagaipov, M M; Gazieva, M Sh; Ferzauli, A I (KnE Life Sciences, 2019)
The article presents the results of studies on the adaptive potential of sorghum used for restoration of degraded pasture ecosystems, increasing their biodiversity and nutritional value. The region chosen for the experiment is a semi-desert arid part of southern Russia. The aridity coefficient is 0.11–0.30 which is typical of the arid zone. The annual volume of precipitation is 125-265 mm. Two varieties of sorghum – Travinka and Caravan – were studied. They were grown with different thickness: 10 thousand, 20 thousand and 40 thousand plants per 1 hectare. During the growing season, there was soil and atmospheric drought. The best indicators of green mass yield were recorded for Travinka for the variant “40 thousand plants per hectare – 7.9 tons per hectare, and for Caravan for the variant “20 thousand plants per hecrate – 3.9 tons per hectare. Compared with natural pasture, sorghum productivity is 18 times higher by green mass yield and 26 times higher by dry mass yield (the best options). The analysis of the chemical composition and nutritional value of sorghum showed that compared to the plants of natural pasture, sorghum is a more nutritious fodder plant. Its nutritional value is more by 0.24 feed units per 1 kg and by 1.9 % by the mass of crude protein. It is better than other plants by the content of sugar content (79 g per 1 kg) and macronutrients.